(untitled) (EU and comparative law issues and challenges series (ECLIC), 2020)
This paper aims to analyze the legal regulation of association registration in the Republic of Croatia and to determine whether the provisions on association registration in the Registry Book of Associations and the acquisition of legal personality of associations have achieved proportionality in the protection of parties’ rights and protection of the public interest. For this purpose, the concept and role of associations in the Republic of Croatia is first considered. Next, the process of establishing and registering associations in the Registry Book of Associations, as a constitutive element of an association acquiring legal personality, is analyzed. Particular attention is thereby paid to the statutory presumption of registration when the competent authority does not issue a decision rejecting the request for association registration within the prescribed period. It probes the justification of such a normative approach and compares it with the legal solutions present in German, French, Italian, Slovenian, and Serbian law. Finally, in conclusion, the authors evaluate the quality of Croatia’s approach to the association registration into the Registry Book of Associations.